Left, right, and meeting in the middle: Addressing addiction is something we can agree about. Issue 4 (1st October 2016) - Narayanan, Arthi K.; Harding, John D.; Saba, Shaddy K.; Conley, James; Gordon, Adam J.
ABSTRACT: The United States faces an addiction health crisis. Presidential election cycles in the United States are cause for creation of political party platforms. These platforms provide general stances and specific policies on a variety of issues. We undertook a review of the addiction policies of the 2016 Republican and Democratic platforms. Despite differences in focus, we found more similarities than differences between the two. We call upon those in political power to use every evidence-based policy at their disposal to promote addiction treatment and prevention.